Conceptions and Perceptions of Software Industry Professionals on Team Productivity in Agile Software Development: A Comparative Study - Guerrero-Calvache, Sandra-Marcela; Hernández, Giovanni (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Agile software development (ASD) has generated different benefits in organizations and in the Software Industry, mainly in improving productivity. For ASD teams this indicator plays a fundamental role since it helps determine their performance. However, evaluating productivity is a great challenge and the way in which this concept has been approached in the literature is very limited. The objective of this article is to contrast the conceptions of productivity at the team level from an ASD perspective with the perceptions that professionals in the software industry have. For the methodological design, the notions of team productivity presented in the literature were identified and compared with the perceptions of 72 professionals from the software industry collected through a survey following the protocol proposed by Kitchenham and Pfleeger. The main results show that the concept of team productivity in the literature is associated with a set of dimensions related to satisfaction, delivery of functional software, and knowledge transfer. On the part of the respondents, a perception of general productivity centered on dimensions of customer satisfaction, activity management, and early identification of the problem to be solved is evidenced. It can be concluded that the professionals' imaginaries focus on presenting productivity from a generic perspective and its dimensions do not necessarily involve teamwork.